2010
DOI: 10.1111/j.1469-8137.2010.03259.x
|View full text |Cite
|
Sign up to set email alerts
|

Global methane emission estimates from ultraviolet irradiation of terrestrial plant foliage

Abstract: Summary• Several studies have reported in situ methane (CH 4 ) emissions from vegetation foliage, but there remains considerable debate about its significance as a global source. Here, we report a study that evaluates the role of ultraviolet (UV) radiation-driven CH 4 emissions from foliar pectin as a global CH 4 source.• We combine a relationship for spectrally weighted CH 4 production from pectin with a global UV irradiation climatology model, satellite-derived leaf area index (LAI) and air temperature data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 55 publications
(93 reference statements)
1
49
0
Order By: Relevance
“…We noted above that it is highly likely that Keppler et al (2006) overestimated the amount of plant CH 4 (with the maximum reported value of 236 Tg CH 4 yr À1 ) and Bloom et al (2010) underestimated it (with the minimum reported value of 0.2 Tg CH 4 yr À1 ). Thus, we adopted here the estimates excluding these two studies of global plant-derived CH 4 and obtained a range of 15e176 Tg CH 4 yr À1 for global plant-derived CH 4 production, suggesting that the CH 4 that terrestrial plants release directly into the atmosphere represents 3%e24% of the global total (Fig.…”
Section: Implications For the Global Ch 4 Budgetmentioning
confidence: 99%
See 2 more Smart Citations
“…We noted above that it is highly likely that Keppler et al (2006) overestimated the amount of plant CH 4 (with the maximum reported value of 236 Tg CH 4 yr À1 ) and Bloom et al (2010) underestimated it (with the minimum reported value of 0.2 Tg CH 4 yr À1 ). Thus, we adopted here the estimates excluding these two studies of global plant-derived CH 4 and obtained a range of 15e176 Tg CH 4 yr À1 for global plant-derived CH 4 production, suggesting that the CH 4 that terrestrial plants release directly into the atmosphere represents 3%e24% of the global total (Fig.…”
Section: Implications For the Global Ch 4 Budgetmentioning
confidence: 99%
“…By assuming UV radiation-induced CH 4 emissions from pectin as representing foliar CH 4 emissions, Bloom et al (2010) suggested a global contribution of 0.2e1.0 Tg plantderived CH 4 yr À1 . However, clear evidence shows that pectin is not the only precursor (Carmichael et al, 2014;Lenhart et al, 2014;Vigano et al, 2009), and several environmental stresses in addition to UV radiation have been observed to induce CH 4 production.…”
Section: Implications For the Global Ch 4 Budgetmentioning
confidence: 99%
See 1 more Smart Citation
“…A global upscaling model for estimating aerobic CH4 emissions, based on lab results and considering only pectin content as a driver has been conducted recently by Bloom et al (2010). Their estimate is one to two orders of magnitude lower than previous estimates of global foliar CH4 emissions by Keppler et al (2006).…”
Section: Introductionmentioning
confidence: 77%
“…In addition, we considered the case of no plant emission (i.e., a third set of estimates), because a general consensus has not yet been reached over the significance of this process (e.g., Bloom et al, 2010).…”
Section: Global Simulation and Analysesmentioning
confidence: 99%